INDIRECT SELF TUNING ADAPTIVE CONTROL OF DOUBLE STARS INDUCTION MACHINE BY SLIDING MODE - HADJI, CHAABANE; KHODJA, DJALAL EDDINE; CHAKROUNE, SALIM (Université de M'sila, 2019)
In this paper we will establish a sliding mode adaptive control based on the direct rotor field control applied to the double stars induction machine. Due to the performance limitations of conventional controllers due to their sensitivities, non-linearity and parametric variations, the indirect "self tuning" adaptive control is applied. Indeed, the recursive least squares algorithm is used to obtain the identification model in order to adapt the RST regulator (three-branched structure regulator) parameters in real time, and then generate the control law. However, the location of the sliding mode regulators to the control chain by indirect rotor flow orientation offers good static and dynamic performance, and almost total rejection of the disturbance. Finally, all the results obtained showed the robustness of the control in front of the variation of the parameters of the system and load.
Keywords: Double star induction machine (DSIM), Sliding mode control (SMC), Indirect self tuning control, RST regulator